Pengaruh Penambahan Bawang Merah (Allium Ascalonicum) Terhadap Penurunan Bilangan Peroksida Dalam Minyak Jelantah - Sulistiyowati, Retno; Al Aajilaini, Sulma (Pena Medika Jurnal Kesehatan, 2017)
Oil is an important food substances, as a source of energy that is more effective than carbohydrates and protein. One gram of oil could yield 9 kcal, while carbohydrates and protein yields only 4 kcal/g.  Cooking oils used repeatedly will damage due to oxidation reactions occur so formed peroxide and pillars. Peroxide number will decrease with the addition of antioxidants which flavonoids found in red onion.This type of research is research experiments with Iodometri method i.e. formation of I2 from KI is added, I2 formed subsequently titrated with Na2S2O3 using amylum indicator. The sample used is waste cooking oil. The optimum concentration of research results obtained in lowering the number of peroxides in the sample is waste cooking oli with oil immersion for 24 hours is a concentration of 75% b/v can decrease the number of peroxides in the sample 1 of 23.42 MekO2/kg MekO2/kg 9.10 becomes with the percentage decrease of 61%, on a sample of 2 is MekO2/kg to 29.15 11.97 MekO2/kg with the percentage decrease of 62%, in sample 3 was 19.56 MekO2/6.20 kg to MekO2/kg with the percentage decrease of 68%.  Anova test results show P = 0.006, there is the influence of the concentration of powder onion against a decline in the number of peroxides. Keywords: waste cooking oil. Red onion, the number of peroxides